2011
DOI: 10.1016/j.ajog.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The “Great Obstetrical Syndromes” are associated with disorders of deep placentation

Abstract: Defective deep placentation has been associated with a spectrum of complications of pregnancy including preeclampsia, intrauterine growth restriction, preterm labor, preterm premature rupture of membranes, late spontaneous abortion and abruption placentae. The disease of the placental vascular bed that underpins these complications is commonly investigated with targeted biopsies. In this review, we critically evaluate the biopsy technique to summarize the salient types of defective deep placentation and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
1,007
2
37

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,271 publications
(1,075 citation statements)
references
References 76 publications
(68 reference statements)
29
1,007
2
37
Order By: Relevance
“…This would be in line with previous histological studies, which indicate an increasing degree of compromised vascular remodeling and obstructive occlusions in the spiral arteries in pregnancies with normotensive IUGR, PE without IUGR, and PE with IUGR25. In addition, in studies that used in‐vivo scintigraphy, reduced placental perfusion compared with normal pregnancy was seen both in pregnancies with IUGR and in those with PE21, 26.…”
Section: Discussionsupporting
confidence: 90%
“…This would be in line with previous histological studies, which indicate an increasing degree of compromised vascular remodeling and obstructive occlusions in the spiral arteries in pregnancies with normotensive IUGR, PE without IUGR, and PE with IUGR25. In addition, in studies that used in‐vivo scintigraphy, reduced placental perfusion compared with normal pregnancy was seen both in pregnancies with IUGR and in those with PE21, 26.…”
Section: Discussionsupporting
confidence: 90%
“…Deficient remodelling of the spiral arteries has been associated with the 'great obstetrical syndromes' [46]. The mechanistic link is strongest in the case of pre-eclampsia, when the resultant malperfusion of the placenta is thought to cause oxidative stress [47].…”
Section: Establishing the Maternal -Placental Circulationmentioning
confidence: 99%
“…It has been shown that insufficient invasion of trophoblast cells into the uterine decidua and inadequate remodeling of the uterine vasculature is associated with preeclampsia, which is a dangerous medical condition characterized by high blood pressure and high levels of protein in the urine of pregnant women (1)(2)(3). Thus, a better understanding of the molecular mechanisms that regulate trophoblast invasion will help to delineate the processes involved in the establishment of pregnancy under normal and pathological conditions.…”
mentioning
confidence: 99%